Publication Trend of Public Sentiment Towards Indonesia Government Policies - Permana, Iip; Maani, Karjuni Dt (Sinkron : jurnal dan penelitian teknik informatika, 2024)
There are 167 million social media users in Indonesia. Some of these users express their opinions on social media known as public opinion. Public sentiment is the classification of public opinion into several classes. Understanding public sentiment through some public policies can benefit the government. Publication trends can be a stepping stone to deeply understanding a research topic. No research was conducted on the publication trend of public sentiment toward Indonesian government policies on social media. This study aims to explore publication trends in the area of public sentiment toward Indonesia government policies on social media using bibliometric analysis. The Scopus database is used to gather abstracts and keywords, funding details, citation information, bibliographical information, and other information. Search document terms used are "public", "sentiment", "social media", "government", governance," and "policy" rolled within the article title, abstract, and keywords. Research publication trends were visualized using VOSViewer co-occurrence keyword analysis, which resulted in seven clusters from all the collected literature. The research trend is climbing significantly in 2018–2021, but decreasing in 2022. The University of Indonesia is the institution that produces the most documents and IOP Conference Series on Earth and Environmental Science is the publication place that publishes the most documents. Decision trees, random forests, logistic regression, naïve bayes, support vector machines and long-short-term memory are part of the machine learning algorithms recycled and Twitter is the most used social media platform.